Cover Picture: A Concentric Ring Electrode for a Wall‐jet Cell in a Microfluidic Device (Electroanalysis 9/2019). Issue 9 (9th September 2019) - Nishiyama, Keine; Hoshikawa, Koki; Maeki, Masatoshi; Ishida, Akihiko; Tani, Hirofumi; Tokeshi, Manabu
Abstract : The cover picture shows a wall‐jet cell with a concentric ring array electrode for a detector of microfluidic devices. This array electrode is operated at a single potential and amplifies the current signal without redox cycling. This electrode delivered a current density that was approximately 50 % higher than that of a conventionally used disc electrode. This array electrode has great potential for use in a variety of applications because it can detect irreversible targets with a simple apparatus at a single potential and requires no electrode modification to achieve high sensitivity. More Details can be found in the Full Paper by Keine Nishiyama, Koki Hoshikawa, Masatoshi Maeki, Akihiko Ishida, Hirofumi Tani, and Manabu Tokeshi (DOI:10.1002/elan.201900109).